The Economic Benefits of Yala Wetland Resources in the Lake Victoria Basin, Threats and Management Strategies for Sustainable Development - Ong`anya, Dedan O. (African Journal of Education,Science and Technology (AJEST), 2023)
Wetlands are the most prolific ecosystems on Earth and provide many vital benefits to humans. Kenya's wetland habitats serve a range of important, interdependent human welfare, ecological, and national development objectives. Many of these are essential for improving human health and well-being and achieving a variety of MDGs and Vision 2030 objectives. The wetland ecosystems of the Lake Victoria basin encompass a vast area and provide a diverse array of economic activities that sustain a considerable proportion of East African people. The Yala wetland is one of the few vast wetland ecosystems found in Lake Victoria Basin. The Yala wetland is the largest freshwater wetland in Kenya. The Yala Wetland is an extraordinarily rich and diversified ecosystem, home to several unique, sensitive, and endangered plant and animal species. The majority of review research has concentrated on the status and challenges of Yala wetland and the wetlands in the Lake Victoria basin. Because of this narrow focus, the major role economic benefits of the Yala wetlands have been given less attention than it deserves. Given this background, the objective of this paper is to review the economic benefits of Yala wetland resources, its threats and its sustainable management. The cconomic benefits of the Yala wetland include fishing, hunting, grazing, agriculture, fuel, and building materials. The threats to the wetland include increasing human population, agricultural activities, encroachment of the wetland, over-exploitation of its natural resources, and climate change. Because of their economic importance to the livelihood of the local populations, Yala wetlands of Lake Victoria need to be conserved and managed in a sustainable manner. Yala Swamp should be restored and rehabilitated wherever possible in conformity with the Ramsar Convention. Value addition on papyrus and its products, practice conservation agriculture including smallholder wetland aquaculture, developing fish value chain with support to hatcheries, local production of fish feeds, and fish processing and marketing. The establishment of an animal sanctuary, commercial tree growing, and integrated organic farming are other initiatives plus several opportunities for sustainable development. In order to promote sustainable wetland management, the study suggests ensuring that wetland use takes into account the various factors outlined in the framework for sustainable use of wetlands; developing and enhancing an appropriate institutional framework; adopting a community-based, multi-stakeholder-based management approach; and enhancing the value of wetlands and their resources by adding value across the entire value chain.